Evaluation of intercanine and intermolar widths in students with mixed dentition, Contulmo Commune, Chile. - Alexandra Harnisch; Juan Vargas; Alexandra Torres; Claudia Fierro; Antonieta Pérez (Universidad de Concepción., 2013)
Introduction: The early orthodontic treatment success is based on knowledge the development of the dentition, so measuring their dimensions at different stages of development is considered as a predictor for treatment and rehabilitation of the population. Objective: To explore and evaluate the quantitative characteristics of intercanine and intermolar widths by sex in the population of children of 6-8 years of the Escuela Artistica San Luis de Contulmo. Methodology: quantitative study, non-experimental, cross-sectional, descriptive and correlational. The study population corresponded to 48 students from 6 to 8 years selected by probabilistic sampling, unintentional and opportunistic, to which took study models, measuring and comparing intercanine and intermolar widths. Results: The resulting averages of measurements were: maxillary intercanine 33.2+2.6mm in men and 32.2+2.3mm in women, mandibular intercanine distances respectively 27.1+2.3mm and 26 6+1.9mm, the distance intermolar maxillary 51.9+3.1 and 51.2+3.0mm and the distance mandibular intermolar 46+2.6 and 44.8+3.0mm. Conclusion: In relation to the difference between intercanine and intermolar widths by sex are not significant, in terms of age significant differences between 6 and 8 males but not in females. This study represents an interesting starting point for the analysis and discussion of future research.